Democracy, Bureaucracy, and the Study of Administration - Camilla Stivers (Westview Press, 2001)
The essays collected in this volume address several of the most central and enduring ideas in the field of public administration. All appeared originally either in Public Administration Review or another of the journals sponsored by the American Society for Public Administration. This volume focuses on themes that cross subdisciplinary and topical boundaries in the field of public administration. They are as relevant to public budgeting as they are to performance measurement, human resource management, and issues of diversity. They are what Dwight Waldo, a former editor of Public Administration Review, referred to as "political theories," that is, they deal with issues that are ultimately unresolvable yet crucial to a sound understanding of the nature of public administration and to good practice. In a real sense, the existence of this volume constitutes a tribute to Waldo, whose vision of public administration as both a set of practical techniques and a political philosophy contributed so much to the subsequent development of the field. Waldo (1948) argued that the tension between democracy and efficiency was the central question in the field of public administration. He believed that it was a tension fated never to be resolved, since administrators are required not only to try to do their work as efficiently and effectively as possible but also to try to conduct themselves in a way that is consistent with democratic values. The idea of "most efficient" or "most effective" practice suggests that administrators, at least over time, can figure out the best way to practice. Yet ideas of democratic administration suggest that, since citizens and their representatives are rarely unanimous about governmental purposes and practices, the single-minded search for a best way is both inappropriate and doomed to failure. As Waldo's view implies, most administrative actions have political implications, because of the power administrators exercise when they make decisions. Thus no matter how hard they search for a best way, their actions will raise debatable political questions. Out of this paradox have grown some of the most important and lasting debates in the field.